2020
DOI: 10.3389/fvets.2020.580649
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Market Analysis Applied to Mini-FLOTAC and Fill-FLOTAC for Diagnosis of Helminth Infections in Ruminants

Abstract: Mini-FLOTAC in combination with the Fill-FLOTAC may be considered a good candidate for a standardized FEC and FECRT in the laboratory, as well as directly in the field, the aim of this study was to conduct SWOT (Strength-Weaknesses-Opportunities-Threats) and PESTEL (Political, Economic, Social, Technological, Environmental, and Legal) analyses of these tools in 20 European countries involved in the COMBAR WG1, in order to identify the opportunities, barriers, and challenges that might affect the Mini-FLOTAC an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
2
9
0
Order By: Relevance
“…Each study center was supplied with tubes (15 ml) pre-filled with 80% ethanol; flea combs and zip-lock bags; one Mini-FLOTAC kit Fill-FLOTAC [ 14 ] containing four Mini-FLOTAC and four Fill-FLOTAC devices (200 tests); and instructions for material collection, conservation and analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Each study center was supplied with tubes (15 ml) pre-filled with 80% ethanol; flea combs and zip-lock bags; one Mini-FLOTAC kit Fill-FLOTAC [ 14 ] containing four Mini-FLOTAC and four Fill-FLOTAC devices (200 tests); and instructions for material collection, conservation and analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Over the past seven years, Mini-FLOTAC (MF) has been used in routine parasitological diagnosis in several animal species, and most of the studies concluded that this technique is a good alternative to the traditional McMaster technique, allowing simultaneous identification of helminth eggs and coccidia oocysts with relatively higher sensitivity, accuracy and precision. Established in the Unit of Parasitology and Parasitic Diseases of the Department of Veterinary Medicine and Animal Production (University of Naples Federico II, Naples, Italy), the manufacturer proposes three MF protocols for animals, namely for small animals (e.g., dogs and cats), herbivores (e.g., ruminants and horses) and exotic species (e.g., birds and reptiles), which involve different fecal dilutions and detection limits [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…McMaster and Mini-FLOTAC [ 37 ], although results rely on operator proficiency. The availability of reliable, low-cost, easy-to-perform tools for swift FEC is of pivotal importance to increase user-friendliness and uptake of FECRT by veterinarians, advisors and farmers [ 66 ]. Different FEC methods apply different dilution factors to faeces, such that higher starting average FEC are needed to ensure robust FECRT results using less sensitive (= higher dilution) methods.…”
Section: Technical Confoundersmentioning
confidence: 99%